Diving: Technique and Timing in the Women's Reverse Two and One Half Somersault Tuck (305C) and the Men's Reverse Two and One Half Somersault Pike (305B) 3m Springboard Dives - Sanders, R.; Gibson, B.; Prassas, S. (Sports Biomechanics, 2002)
The purpose of this study was to compare the reverse two and one half somersault dive in a tuck position (305C) performed by females (n = 24) and the reverse two and one half somersault dive in a pike position (305B) performed by males (n = 21), to determine changes required by females to successfully perform 305B. Key performance variables in reverse dives were also compared to those of forward dives. Video data of the dives performed in the 1999 FINA World Diving Cup were captured and digitised to obtain times and postures of the divers at specific events including hurdle landing, takeoff, and entry. Estimates of hurdle flight height and mass-normalised work done on the springboard were obtained from hurdle and flight times. The males did more work on the springboard to achieve greater height and rotation than females. Females performing 305C had less hip and knee flexion at hurdle landing than males performing 305B and took longer to achieve maximum hip flexion after takeoff from the springboard. To progress from 305C to 305B females need to adjust their techniques to put more energy into the system. Desirable changes include increased height in the hurdle and increased hip and knee flexion prior to hurdle landing. Comparison of results for reverse dives with data previously presented for forward dives indicated that divers are more limited in the number of somersaults and dive position in reverse dives than forward dives despite equivalent or better height in reverse dives than forward dives.